Teacher and student perception of integrated science literacy in information, technology, and environtment - Hamidah, Idah; Luzyawati, Lesy; Ratnasari, Anilia (Jurnal Mangifera Edu, 2025)
The development of technology and information in the 21st century is increasing rapidly. Meanwhile, Indonesia's science literacy levels remain categorized as low. Science literacy is among the most essential skills in the 21st century, so integrated technology, information, and environment are fundamental. This research aims to understand the perception of teachers and students towards science literacy integrated with technology, information, and environmental literacy in Junior High Schools (SMP). This research falls under the quantitative category and employs an observational descriptive design. The sample in this study consists of three junior high schools in the Indramayu Regency, representing the Indramayu region's western, central, and eastern regions. The questionnaire instrument determines students' science literacy ability towards information, technology, and the environment. Meanwhile, interviews were used to determine teachers' and students' perceptions of information-based science literacy, technology, and the environment. The research data were obtained using both questionnaires and interview instruments. The study results reveal that the integration of science literacy with information, technology, and the environment achieved percentages of 69.42% for information-integrated science literacy, 70.98% for technology-integrated science literacy, and 73.89% for environment-integrated science literacy, highlighting varying levels of proficiency across these domains. This indicates a moderate ability to integrate science literacy effectively.